Theoretical analysis of attosecond quantum beat spectroscopy of helium excited states. (August 2015) - Zimmermann, T; Landsman, A S; Lucchini, M; Ludwig, A; Kasmi, L; Herrmann, J; Gallmann, L; Scrinzi, A; Keller, U
Synopsis: Photoelectron spectra measured in the attosecond quantum beat spectroscopy experiment on helium were computed solving the single-electron time-dependent Schrdinger equation. Final momenta of photoelectrons were obtained from the probability flux at the boundary of the simulation region using the time-dependent surface flux (t-SURFF) method [1]. Reaching a very good agreement with the experimental results, simulations allow for deeper understanding of processes underlying the quantum beating, which-way interference and polarization of the excited state.